Implementation and Outcomes of the New York State YMCA Diabetes Prevention Program: A Multisite Community-Based Translation, 2010–2012 - Bozack, Anne (Centers for Disease Control and Prevention, 2014)
INTRODUCTION: Weight loss and physical activity achieved through the Diabetes Prevention Program (DPP) have been shown to reduce type 2 diabetes risk among individuals with prediabetes. The New York State Young Men’s Christian Association (YMCA) delivered the 16-week evidence-based model at 14 YMCAs. A mixed methods process and outcomes evaluation was conducted. METHODS: Most participants were referred by clinicians and were encouraged to achieve 5% to 7% weight loss. Participants were weighed weekly; additional data were gathered from participant surveys and focus groups and staff surveys and interviews. RESULTS: Participants (N = 254) lost a mean of 9 pounds (P < .001), or 4.2% of body weight, by program completion; 40% achieved 5% or more weight loss and 25% achieved 7% or more weight loss. Ten months after baseline, 61% of participants reported 5% or more weight loss and 48% reported 7% or more weight loss. In multivariate models, weight loss was negatively associated with black race (16 weeks: adjusted odds ratio [AOR], 0.190, P = .002; 10 months: AOR, 0.244, P = .005) and positively associated with attendance (16 weeks: AOR, 18.699, P < .001; 10 months: AOR, 2.808, P = .024). Participants reported improvements in health and lifestyle changes after program completion. Factors contributing to program success included coaches who motivated participants, the group setting, curriculum, and program duration. However, sociodemographic diversity was limited. CONCLUSION: Outcomes demonstrate the potential for effectively implementing the DPP in community-based settings. Findings also suggest the need for replications among a broader population.